Adaptive Resource Allocation of Vehicles under Dynamic Environment. (4th May 2022) - Du, Lei; Huo, Ru; Sun, Chuang; Wang, Shuo; Guo, Jie; Huang, Tao
Abstract : With the rapid development of the Internet of Vehicles (IoV), the capabilities and intelligence of vehicles are rapidly increasing, which will have the potential to support a large number of services for the users of vehicles. However, taking into account the mobility of the vehicle, how to combine the computing resources from nearby vehicles with high mobility and RSUs to provide services collaboratively is a crucial problem. In this paper, we propose an adaptive allocation scheme of computing resources to allocate the resources more reasonably. First, the vehicular mobility model is built to predict the trajectory of vehicles. Second, the sub-networks to execute the V2V communication are constructed according to the prediction of trajectory. Third, the allocation of computing resources from nearby vehicles and RSUs is formulated as an optimization problem and the intelligent optimization algorithm is employed to deal with it. The relative experiments are conducted to verify the effectiveness of the proposed method.